Understanding Religion and Spirituality in Clinical Practice. - Clark, Margaret (The Society of Analytical Psychology monograph series, 2011)
Understanding Religion and Spirituality in Clinical Practice is a volume in the clinical practice monograph series from the Society of Analytical Psychology. This series is intended primarily for trainees on psychotherapy and psychodynamic counselling courses, and for those who are newly qualified. Here, Margaret Clark considers the difficulties clinicians may encounter when patients talk about God or about their spiritual life, and how necessary it is for therapists to examine their own image of God and their own understanding of spirituality, so that they can distinguish these from those of t.